Pola Manejemen Kelas Guru Sekolah Dasar Di Kota Surabaya Terhadap Persoalan Motivasi Belajar Siswa Rendah - Wahyuni, Holy Ichda; Budiman, Agus (Anterior Jurnal, 2024)
Learning in elementary schools involves various challenges and problems, especially those related to students' developmental characteristics. Teachers are expected to be able to design and implement learning that is appropriate to students' cognitive, social and emotional development. Students' learning motivation in elementary schools can be a serious obstacle, affecting the achievement of learning outcomes. Classroom management is considered the key to creating an effective learning atmosphere and motivating students. This research aims to determine the classroom management patterns implemented by elementary school teachers in the city of Surabaya regarding the problem of low student learning motivation. This research is qualitative research with a multi case study type, using the Explanatory Survey method. The informants consisted of 23 elementary school teachers in the city of Surabaya, selected using a cluster random sampling technique. Data collection was carried out through interviews, and data analysis was carried out descriptively qualitatively. The research results show that the main obstacle in learning is students' passivity and noise which is triggered by low learning motivation. Some teachers apply a Student-Centered Learning (SCL) approach to overcome this problem, placing students as active subjects. Classroom rules, learning contracts, and inspirational stories are considered effective classroom management strategies. Teachers also provide interactive feedback and emphasize an emotional approach to increase students' sensitivity.